The `Bauer bump:` ice hockey skates as a common cause of Haglund syndrome - Desai, S. S.; Wong, T. T.; Crockatt, W. K.; Tedesco, L. J.; Trofa, D. P.; Popkin, C. A. (The Physician and Sportsmedicine, 2023)
Ice hockey is a fast-paced contact sport with a high rate of injury. While many of the injuries are acute and related to high skating speeds, frequent collisions, and sharp skates, the clinician must also be aware of the chronic injuries that commonly arise from playing this sport. The "Bauer bump" is one such chronic injury, which is the onset of Haglund syndrome in ice hockey players occurring in the context of wearing ice hockey skates. With this condition, players notice a bony enlargement of their posterosuperior calcaneus with or without the accompanying symptoms of retrocalcaneal bursitis and insertional Achilles tendinopathy. It is important for clinicians to understand the nature of Haglund syndrome in hockey players so that it can be appropriately diagnosed, managed, and ultimately, prevented.